Impact of Time Delay on Short Term Outcome of Primary Percutaneous Coronary Intervention (PCI) in Bangladeshi Population (University Heart Journal, 2019)
Background: Now-a-days primary percutaneous coronary intervention (pPCI) is being increasingly done in our country as the treatment of acute ST elevation myocardial infarction (STEMI). Time until treatment is paramount in the management of STEMI. But the time delay to pPCI how much influencing the outcome in our setting is mostly unknown.So we evaluated the influence of total ischemic time on myocardial reperfusion and short term clinical outcome in patients with STEMI treated with primary PCI.Materials and methods: This prospective observational study was conducted from August 2016 to March 2017in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka. Forty-eight (48) acute STEMI patients were selected by purposive sampling based on inclusion and exclusion criteria dividing into two groups as early treatment group (group-A) in whom pain to pPCI time was